OCA Oracle database 11g SQL fundamentals I exam guide (exam 1Z0-051) - Watson, John 1946 April 5- (McGraw-Hill, 2008)
"Prepare for the Oracle Certified Associate Oracle Database 11g: SQL Fundamentals I exam with help from this exclusive Oracle Press guide. In each chapter, you'll find challenging exercises, practice questions, a two-minute drill, and a chapter summary to highlight what you've learned. This authoritative guide will help you pass the test and serve as your essential on-the-job reference"--Resource description page
Title from PDF title page (viewed July 15, 2008). - Excludes information from CD-ROM that accompanied the print version of the book. - Includes index
Keywords: Oracle (Computer file) -- Examinations; Electronic data processing personnel -- Study guides -- Certification; Oracle (Computer file) / Examinations; Oracle (Computer file); COMPUTERS; Programming Languages; SQL; Electronic data processing personnel; Certification; Study guides; Electronic data processing personnel; Certification; examination study guides; Examinations; Study guides; Guides de l'étudiant